REALIZATION OF STRATEGIC GOALS OF SUBSTITUTION OF IMPORT OF MAIZE HYBRID SEEDS ON THE TERRITORY OF RUSSIA FEDERATION - A. A. Maremukov (Зерновое хозяйство России, 2018)
Maize is one of the principal crops, which supplies food safety of the Russian Federation. The strategic goal to substitute import of maize seeds in the country has been put. The further increase of maize production is planned due to the increase of its productivity, which is going to be achieved by using highly productive maize hybrids and by cultivating them with the economically feasible adaptive to landscape technologies. The domestic maize hybrids developed by the researchers do not concede to foreign analogues in productivity and they are better adapted to the various soil-climatic conditions of the country and can be sown in the North-Caucasus, Southern, Central and Pre-Volzhie Federal Areas and in other regions of the European part of Russia. At present 86 000 ton of maize seeds (56% of which are of domestic selection) are sown annually in Russia. To increase the production of the crop up to 25 mln ton till 2020 it’s necessary to increase domestic production more than twice. In the Republic of Kabardino-Balkaria we produce maize hybrid seeds of all types of maturity due to its weather-climatic conditions. Annually we produce 15-18 000 ton of maize hybrids that is 20% of the total demand of seed market. They are supplied to 31 regions of the country and to the Republic of Belarus. Kabardino-Balkaria possesses a potential to increase maize seed production. The maize seed production in the republic is going to be increased up to 32 000 ton till 2020, that will supply about 30% of cultivated areas of the Russian Federation with the seeds. The further increase of grain production is an important governmental goal and its fulfillment depends on the assurance of food safety in the North-Caucasus region and in the Russian Federation on the whole.